Electromagnetic Interference Shielding Effectiveness of Clay, Alumina, and Carbon Nanotubes Based on Epoxy Nanocomposites - dos Reis F.C. (2024)
© 2024 Universidade Federal de Sao Carlos. All rights reserved.In this work, epoxy resin-based composites reinforced with nanoclays, nanoalumina, carbon nanotubes (CNTs) (0.15, 0.50, and 1.50% vol were submitted to morphological characterization by scanning (SEM) and transmission (TEM) electron microscopies, electrical tests through electrical impedance spectroscopy, and electromagnetic analyses (scattering parameters), in the frequency range of 8.2 to 12.4 GHz. SEM images of the CNT composite revealed nanotube clusters in the matrix. The proximity between the CNTs is corroborated by the increase in the electrical conductivity of the composite due to the formation of a long-range electron transport network, which favored the polarization effect, absorption losses (SEA = 1.33 dB), reflection (SER = 3.38 dB) and reflection loss (RL = -6.61 dB at 10.8 GHz). Composites with nanoclays and nanoalumina showed no significant electrical and electromagnetic results.